2015
DOI: 10.21275/v5i5.nov163554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Malaria and ABO Blood Group Types

Abstract: Abstract:Introduction: There is a paucity of studies on the relationship between ABO blood group and its influence on malarial infection. This study was undertaken to study the relationship of severity of malaria with blood groups and to evaluate if ABO blood groups show differential susceptibility to falciparummalaria. Methods: In 200 malaria positive patients, blood group analysis was done. Patients with at least one of the following complications was considered complicated malaria cases, ie: cerebral malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…This study was aimed at investigating the role of ABO blood types on malaria risk among the Chinese people. However, no statistically significant relation was found between malaria prevalence and ABO blood types, which was consistent with previous studies [2, 3, 11]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study was aimed at investigating the role of ABO blood types on malaria risk among the Chinese people. However, no statistically significant relation was found between malaria prevalence and ABO blood types, which was consistent with previous studies [2, 3, 11]. …”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with previous studies, which reported a high frequency of blood group O in tropical regions with rampant malaria [3, 9, 11, 12]. However, contrary to our observation, Deepa et al [13] stated blood group B as the dominant blood type in their study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The 'A' and 'B' blood group tri saccharides are thought to operate as receptors and are a crucial factor in rosetting on uninfected RBCs. They bind to parasite rosetting ligands such PfEMP-1 and trigger sequestering [69]. In comparison to blood groups A, B, and AB, RBCs of blood group 'O' do not express trisaccharide, and rosettes generated by infected 'O' blood group RBCs are smaller and more easily destroyed.…”
Section: Abo-blood Group VIImentioning
confidence: 99%